2002
DOI: 10.1002/pds.733
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen replacement therapy and risk of lung cancer

Abstract: Our data do not support an increased risk of lung cancer among women who use ERT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
45
1
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 15 publications
0
45
1
1
Order By: Relevance
“…26 Schabath et al 27 found HRT use within the previous 6 months was associated with a reduced lung cancer risk. In our study, we defined HRT use as ever use of HRT for 3 months or more, which is similar to the definition by Blackman et al 23 The association of HRT and reduced lung cancer risk could be found in studies with different durations of HRT use. The relation between the duration of HRT use and lung cancer risk is unclear and may required further study.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…26 Schabath et al 27 found HRT use within the previous 6 months was associated with a reduced lung cancer risk. In our study, we defined HRT use as ever use of HRT for 3 months or more, which is similar to the definition by Blackman et al 23 The association of HRT and reduced lung cancer risk could be found in studies with different durations of HRT use. The relation between the duration of HRT use and lung cancer risk is unclear and may required further study.…”
Section: Discussionmentioning
confidence: 88%
“…A recent Canadian cohort study demonstrated that long-term HRT use is associated with increased risk of lung cancer. 22 However, the Women's Health Initiative study 17 and a hospitalbased case-control study 23 found no association between HRT use and lung cancer. A nested casecontrol study by Elliott and Hannaford found a nonsignificant reduction of lung cancer risk for HRT users.…”
mentioning
confidence: 99%
“…A second cohort study of estrogen replacement therapy 22 found a nonsignificant reduction in risk of lung cancer after adjusting for smoking (RR 5 0.22, 95% CI 0.04-1.15). Additionally, in a large hospital-based case-control study 26 carried out in a population using predominantly estrogen preparations, ever use of estrogen replacement therapy or of conjugated estrogens was not associated with increased lung cancer risk; nor was there an association with duration of use or with specific histologic types. A second cohort study from Sweden, 25 24 However, follow-up of this cohort was rather short (mean of 5.2 years).…”
Section: Discussionmentioning
confidence: 94%
“…Eleven studies have reported on the association of HRT and risk of lung cancer. 18,19,21,22,[24][25][26]28,30,31,35 Most of these studies do not define whether their results pertain to estrogen alone or estrogen plus progestin. One early cohort study from Sweden, 19 which assessed exposure to both potent estrogens and weaker Each factor is adjusted for all other factors, including for parity (4 levels), age at menarche (4 levels), menopausal status (pre-, peri-and postmenopausal), oral contraceptive use (ever/never), hormone replacement use (ever/never), body mass index (continuous), education (3 categories), smoking status (never, former smoker and current smoker), pack-years of smoking (continuous), study center and randomization group (intervention versus control).-2 Among parous women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation